Comparison of humoral response in sheep to Fasciola hepatica and Fasciola gigantica experimental infection - Zhang W.; Moreau E.; Huang W.; Chauvin A. (Parasite, 2004)
Humoral response of sheep to F. gigantica was compared with the well known humoral response to F. hepatica, in order to explain the difference of susceptibility of sheep to these two parasites. In this work, a lesser susceptibility of sheep to F. gigantica than to F. hepatica infection was confirmed. Humoral response to F. hepatica infection is similar to that previously described by several authors. IgG level of F. gigantica infected sheep increased from week 2 post-infection (2WPI) and displayed a peak at 13WPI. F. gigantica excretory-secretory products (FgESP) analyzed by SDS-PAGE showed at least 31 bands from 12.0 to 127.6 kDa in FgESP. Western blot indicated that F. gigantica infected sheep sera recognized, in FgESP, at least 30 antigens from 7.8 to 119.2 kDa of which 12 major bands recognized after OWPI. In FhESP and FgESP, F. hepatica infected sheep serum reacted only with the lower molecular mass antigens, while F. gigantica infected sheep serum reacted with the lower and the higher molecular mass antigens. These differences of antigenic recognition might be associated with the difference of susceptibility of sheep. Further investigation must be done to study the mechanism of resistance between the sheep infected with F. hepatica or F. gigantica.